Pengaruh Tingkat Upah Dan Investasi Terhadap Tingkat Pengangguran Di Kabupaten Timor Tengah Utara - Oki, Kamilaus Konstanse; Nalle, Frederick W.; Nenokeba, Novianty (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2020)
The application of wage levels in the district of Timor Tengah Utara has not yet adhered to government regulations as stipulated in the Provincial Minimum Wage. Most workers only hope for employment provided by the government through the recruitment of State Civil Apparatuses by prospective workers who have formal education. Employment opportunities opened by private parties through private companies in the district of Timor Tengah Utara are still very limited. As a result of these real conditions, the unemployment rate in Timor Tengah Utara district is still high. Speculation carried out by the community to achieve family welfare is to exploit the potential and opportunities of the border market and to speculate into labor outside the region or abroad legally and illegally with various risks